Consumption of sugar-sweetened and artificially sweetened soft drinks and risk of obesity-related cancers. Issue 9 (21st February 2018) - Hodge, Allison M; Bassett, Julie K; Milne, Roger L; English, Dallas R; Giles, Graham G
Abstract: Objective: To test the hypothesis that more frequent consumption of sugar-sweetened soft drinks would be associated with increased risk of obesity-related cancers. Associations for artificially sweetened soft drinks were assessed for comparison. Design: Prospective cohort study with cancers identified by linkage to cancer registries. At baseline, participants completed a 121-item FFQ including separate questions about the number of times in the past year they had consumed sugar-sweetened or artificially sweetened soft drinks. Anthropometric measurements, including waist circumference, were taken and questions about smoking, leisure-time physical activity and intake of alcoholic beverages were completed. Setting: The Melbourne Collaborative Cohort Study (MCCS) is a prospective cohort study which recruited 41 514 men and women aged 40–69 years between 1990 and 1994. A second wave of data collection occurred in 2003–2007. Subjects: Data for 35 593 participants who developed 3283 incident obesity-related cancers were included in the main analysis. Results: Increasing frequency of consumption of both sugar-sweetened and artificially sweetened soft drinks was associated with greater waist circumference at baseline. For sugar-sweetened soft drinks, the hazard ratio (HR) for obesity-related cancers increased as frequency of consumption increased (HR for consumption >1/d v . <1/month=1·18; 95 % CI 0·97, 1·45; P -trend=0·007). For artificially sweetened soft drinks, the HR for obesity-related cancers was not associated with consumption (HR for consumption >1/d v . <1/month=1·00; 95 % CI 0·79, 1·27; P -trend=0·61). Conclusions: Our results add to the justification to minimise intake of sugar-sweetened soft drinks.